2000
DOI: 10.1097/00002030-200003310-00005
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the reasons for discontinuation of the first highly active antiretroviral therapy (HAART) regimen in a cohort of antiretroviral naïve patients

Abstract: If the current HAART regimen caused no toxicity, less than 10% of naïve patients discontinue their first HAART regimen because of failure after 1 year from starting therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
239
3
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 509 publications
(271 citation statements)
references
References 21 publications
21
239
3
4
Order By: Relevance
“…The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity. 7 In the current study, 1026 of 1852 (55%) regimens were discontinued by 1 year and nearly half of these regimen discontinuations (458 of 1026 regimens) were due to toxicity attributed to antiretroviral medications.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity. 7 In the current study, 1026 of 1852 (55%) regimens were discontinued by 1 year and nearly half of these regimen discontinuations (458 of 1026 regimens) were due to toxicity attributed to antiretroviral medications.…”
Section: Discussionmentioning
confidence: 65%
“…1,7,[9][10][11][12][13][14] The most frequently reported side effects are gastrointestinal, including nausea, vomiting, and diarrhea. The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations